Possible TRALI is a real entity. Issue 10 (10th July 2017) - Juffermans, Nicole P.; Vlaar, Alexander P.
Abstract : After the consensus definition of transfusion‐related acute lung injury (TRALI), studies have shown that the incidence of TRALI is high in critically ill and injured patients. When another risk factor for lung injury is present in these patients, the term "possible TRALI" is used. In the past years, both animal and clinical studies have taught us that a predisposing inflammatory risk factor is frequently present in TRALI, if not mandatory. The decline in the incidence of TRALI after implementation of the use of male‐only plasma as observed in general hospital patients is also seen in the critically ill and injured, suggesting that antibodies play a role in possible TRALI. Thereby, introduction of the term "possible TRALI" has helped us in estimating incidence rates as well as to understand risk factors for TRALI in patient populations with a high exposure to transfusion.